The role of paddy cultivation in the development of agro economic of thenmaradchi division - Saranya, S.; Subajini, U. (University of Jaffna, 2019)
Thenmaradchy, which is one of the secretarial divisions within the district if Jaffna, produces the highest amount of paddy within Jaffna peninsula. Since paddy cultivation is the main source of the economy here, this study focuses on the contribution made by paddy cultivation to the economy of this region. The main problem identified here is that the cultivation are unable to make up their profits, in keeping with their increasing up costs of production. The object of this study includes the extent of land under paddy cultivation. Periodical variation in the production of paddy identifying locational distribution, the role of paddy cultivation in the economy and the problems faced by farmers, and to suggest ways to reduce them in order to increase the role of paddy cultivation in the sphere of economy. Encompassing the period from 2010 to 2018 primary data were collected through direct observations, interviews, focus group discussion, questionnaires and Participatory field study. Secondary data include statistical and digital data under the GIS. Based on the secondary data obtained from questionnaires six villages were selected based on a purpose sampling from both agricultural service centers of the region. Cultivators were selected at random representing 12% of the cultivators having membership in the farmer groups growing paddy in the most considerable hectare extents. The data obtained from them were mapped through excel software while locational distributions were mapped using GIS (Arc map 10.4). An analysis was carried out including the role paddy cultivation in the economy of the region and the problems faced by the farmers. The ways and means to reduce them while increasing the contribution from agriculture were analyzed using quantitative and quantitative explanatory methodology. The conclusion of the study includes the total extent of land under cultivation and the periodical increases and changes in production. The locational distribution of paddy cultivation varies from village to village. The production of paddy in lands belonging to individual cultivators is deficient. Through paddy cultivation in this region faces physical as well as human, problems, since it contributes to 88 % of regional economy ways, and solutions have been put forward in such a way as to promote the future development of paddy cultivation in this region.
Keywords: Regional secretarial division; Economic development; Locational and periodic distribution; Geographical information system